Cocrystal structure of progesterone-isophthalic acid, C25H33O4 - Wang Peiyu; Sun Ruiqin; Yang Xuguang (Zeitschrift für Kristallographie - New Crystal Structures, 2024)
C25H33O4, monoclinic, I2 (no. 5), a = 15.8319 Å, b = 7.4609 Å, c = 19.2676 Å, β = 103.162°, V = 2216.11(5) Å3, Z = 4, Rgt(F) = 0.0323, wRref(F2) = 0.0936, T = 297(7) K.